Importance of biometric aspects in breeding selection: review - Castelo Branco , Yndyra; Silva, Maisy Cordeiro da; Cruz, Daniela Menezes da; Lima, Rodrigo Cruz de Freitas; Branco, Marlon de Araújo Castelo; Gomes, Leopoldina Almeida; Nascimento, Isolda Márcia Rocha do; Simplício, Kalina Maria de Medeiros Gomes; Lima, Paula Regina Barros de (Pubvet, 2020)
The testis is an organ that has exocrine function related to sperm production, storage and transport, and endocrine function related to androgen hormone production. In the search for good breeders, testicular morphometric characteristics such as scrotal circumference have been evaluated, however, it is not enough to make a selection, using other parameters such as volume and testicular length. With this in mind, the aim of this review is to address the influence of biometric factors and their relationship with testicular morphology and seminal quality for breeding evaluation.